Réponses

2013-04-04T16:52:05+02:00

9) (-5)*(-5)*(-5)=(-5)^{3} \\ \\\frac{1}{5*5*5}=5^{-3} \\ \\(-3)*(-3)*(-3)*(-3)*(-3)=(-3)^{5} \\ \\\frac{1}{3*3*3*3*3}=3^{-5}

 

7)a) \frac{1}{3^{7}}=3^{-7}

 

7)b) \frac{1}{5^{9}}=5^{-9}

 

7)c) \frac{1}{(-6)^{4}}=(-6)^{-4}

 

7)d) \frac{1}{7^{3}}=7^{-3}

 

7)e) \frac{1}{(-4)^{5}}=(-4)^{-5}

 

8)a) 2^{-3}=\frac{1}{2^{3}}=\frac{1}{2*2*2}=\frac{1}{8}

 

8)b) 2^{-4}=\frac{1}{2^{4}}=\frac{1}{2*2*2*2}=\frac{1}{16}

 

8)c) 3^{-3}=\frac{1}{3^{3}}=\frac{1}{3*3*3}=\frac{1}{27}

 

8)d) 5^{-2}=\frac{1}{5^{2}}=\frac{1}{5*5}=\frac{1}{25}

 

8)e) 2^{-1}=\frac{1}{2^{1}}=\frac{1}{2}

 

8)f) 9^{-1}=\frac{1}{9^{1}}=\frac{1}{9}

 

8)g) (-2)^{-3}=\frac{1}{(-2)^{3}}=\frac{1}{(-2)(-2)(-2)}=-\frac{1}{8}

 

8)h) (-1)^{-3}=\frac{1}{(-1)^{3}}=\frac{1}{(-1)(-1)(-1)}=-\frac{1}{1}=-1